ANALYSIS OF CITY BRANDING OF THE OLD CITY OF PADANG BY THE PADANG HERITAGE COMMUNITY IN INCREASING HISTORICAL AND CULTURAL TOURISM INTEREST - Marta, Revi; Rizaldi, Achmad; Havifi, Ilham; Roem, Elva Ronaning (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Kota Tua Padang, as a city branding icon, has great potential as a historical and cultural tourism destination, but the government's efforts in branding this area are still not optimal. The Padang Heritage Community, through programs such as the Padang Heritage Walk, plays an important role in increasing tourist interest in the history and culture as well as the branding of Kota Tua Padang. This research aims to deeply understand how the Padang Heritage Community conducts city branding through the Padang Heritage Walk program and analyze the persuasive messages conveyed. This research uses a case study approach by collecting data through interviews, observation, and documentation, and analyzing the data qualitatively. The results show that Padang Heritage Community, through the Padang Heritage Walk program, has played an important role in the city branding process of Kota Tua Padang. They have succeeded in reviving this historical area through interactive and educational activities, as well as building a positive image of the area as a tourist destination rich in historical and cultural values. For the persuasive messages delivered by the Padang Heritage Community, they have successfully created a positive impact on the image of Kota Tua Padang as a historical and cultural tourist destination.